2015
DOI: 10.3892/etm.2015.2807
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of severe aplastic anemia immunosuppressive therapy and human leukocyte antigen alleles in pediatric patients

Abstract: Abstract. The aim of the present study was to investigate the correlation between the efficacy of immunosuppressive therapy (IST) in children with severe aplastic anemia (SAA) and human leukocyte antigen (HLA) alleles. The polymerase chain reaction-sequence based typing high-resolution genotyping method was used to profile the HLA alleles of 115 SAA cases that were treated with rabbit-antithymocyte globulin (r-ATG) + cyclosporine (CsA) immunosuppressive therapy and 222 normal control subjects. The aim was to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…From the results of this study, the allele frequencies of the HLA loci in the population enrolled in this study were fundamentally the same as previously reported. For example, in this study, the alleles with frequencies of more than 10% at HLA-A locus were A*1101 (19.14%), A*2402 (18.18%), and A*0201 (12.87%), which was similar to Hei AL et al [3] and Deng YJ et al [12] , and was also consistent with the frequencies…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…From the results of this study, the allele frequencies of the HLA loci in the population enrolled in this study were fundamentally the same as previously reported. For example, in this study, the alleles with frequencies of more than 10% at HLA-A locus were A*1101 (19.14%), A*2402 (18.18%), and A*0201 (12.87%), which was similar to Hei AL et al [3] and Deng YJ et al [12] , and was also consistent with the frequencies…”
Section: Discussionsupporting
confidence: 89%
“…Many researches have reported the difference in HLA allele frequency between hematological disease patients and healthy volunteers. For example, Fu RT et al [13] found that HLA-B*1502, -B*1511, -DQB1*0303 and -DQB1*0602 had correlation with the effects of immunosuppressive therapy in severe pediatric aplastic anemia patients. Al-Tonbary Y et al [14] reported that HLA-DQB1*0201 might be the susceptible gene in Non-Hodgkin's lymphoma, while HLA-DQB1*0502 and -DQB1*0602 might be protective genes for it.…”
Section: Table 5 Common (Hf>2%) Hla Two-locus Haplotypes In 663 Familiesmentioning
confidence: 99%